ANALYSIS OF THE DRIVING OF THE CUTTING MECHANISM FOR BAND SAW - Sokolovski, Slavcho; Deliiski, Nencho (Innovation in Woodworking Industry and Engineering design, 2012)
Analysis of the driving of the cutting mechanism for band saw is provided. The forces exercising an effort on the main band saw shaft resulting from the cutting of the band saw and the V-belt gear are determined. Validating calculations on static strength and fatigue of the main drive belt of the band saw are made.